Rhythms of Learning in NGO-Supported Village Associations in Western Uganda - Ahimbisibwe, Karembe F.; Aganyira, Kellen; Nampijja, Dianah; Mudondo, Constance; Achen, Stella (Routledge, 2025)
This article explores how a non-governmental organisation (NGO) facilitates patterns of learning, unlearning, and relearning and, in so doing, strengthens people’s livelihoods in rural Uganda. We conceptualise how NGO-supported village associations become avenues for learning trajectories that potentially “free” citizens from perpetual poverty. Based on qualitative data collected from members of village associations in western Uganda, we illustrate how a local NGO facilitates learning new knowledge, unlearning prevailing habits and practices, and relearning for gradual self and community improvement. Drawing on Alhadeff-Jones's (2017; 2019; 2020) conceptualisation of rhythms of time and space and emancipation, we coin the term “rhythms of learning” to analyse how marginalised citizens collectively – and incrementally – learn to improve their livelihoods under the aegis of an NGO. This analysis provides insights to development practitioners on how to promote incremental learning and change in illiberal settings where radical transformation of power structures is circumstantially difficult. International Bibliography of the Social Sciences (IBSS)
Keywords: Village associations; emancipation; NGOs; western Uganda; rhythms oflearning